Relationship some Motor and Mental Games On The Motor for 5 Year Old Childre - Abd, Amira; Karim, Fatima (Journal of Physical Education, 2014)
The importance of the study lies in using motor games for physical education because they are very interesting and motivating for environment enables them to achieve their motor, cognitive and physical potentials. Thus the importance lies in identifying the child’s creativity through his involvement in motor activity. The aims of the study: Designing a set of motor games that improve motor creativity in 5 year old children.& Identifying the effect of some motor games that improve motor creativity in 5 year old children. &Identifying gender differences in motor creativity improvement. The researcher used the experimental method. The subjects were (40) five year old children from Al Hekma Kindergarten.. The experiment included 30 sessions. The data were collected and treated using SPSS. Finally the researcher concluded the following: 1. Motor Games’ Program had a great effect on motor creativity improvement for five year old children 2. There are differences between male and female children in the experimental group in favor of females in motor creativity improvement